Coxibs, Traditional NSAIDs, and Cardiovascular Safety Post‐PRECISION: What We Thought We Knew Then and What We Think We Know Now. Issue 2 (26th May 2017) - Patrono, C; Baigent, C
Abstract : The aim of the present review is to analyze how thinking about the cardiovascular safety of nonsteroidal antiinflammatory drugs has evolved during the past two decades, and discuss to what extent the additional information from the Prospective Randomized Evaluation of Celecoxib Integrated Safety Versus Ibuprofen or Naproxen study may alter our current mechanistic understanding and/or clinical practice.